An estimate of the approximate solution to a problem of linear optimal filtration - Kolos, I.V.; Kolos, M.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2007)
The problem of signal restoration in systems with operator coefficients is considered in the presence of approximate initial data and degenerate white noise in measurements. A method for finding an approximate solution to this problem is proposed. The method is based on Tikhonov’s regularization. The convergence of the algorithm is proved and estimates for the approximate solution is obtained.